A pilot study comparing optical coherence tomography, radiography, clinical photography, and polarisation microscopy for studies of hypomineralisation disturbances in enamel. Issue 2 (February 2023) - Solgaard Henriksen, Josephine; Lauridsen, Eva; Gjørup, Hans; Al-Imam, Hiba; Lundgren, Ted; Sabel, Nina; Robertson, Agneta; Spin-Neto, Rubens; Hermann, Nuno Vibe
Abstract: Aim: To investigate the use of optical coherence tomography (OCT) as a tool to assess general and localised hypomineralisation defects in the enamel. Design and Materials: Ten extracted permanent teeth (four teeth with localised hypomineralisation, four teeth with general hypomineralisation, and two healthy controls) were used in this study. In addition, four participants who underwent OCT served as living controls for the extracted teeth. Methods: The OCT results were compared with clinical photographs, digital radiographs, and polarising microscopy images of tooth sections (considered the gold standard) to determine the method with the most accurate information regarding the extent of enamel disturbances: 1) visibility of enamel disturbance (visible yes/no); if yes, 2) extent of the disturbance in the enamel; and 3) determination of the plausible involvement of the underlying dentin. Results: OCT was more accurate than digital radiography and visual assessment. OCT could provide information about the extent of localised hypomineralised disturbances in the enamel that was comparable to that with polarisation microscopy of the tooth sections. Conclusion: Within the limitations of this pilot study, it can be concluded that OCT is suitable for investigating and evaluating localised hypomineralisation disturbances; however, it is less useful in cases with generalised hypomineralisation of the enamel. In addition, OCT complements radiographic examination of enamel; however, more studies are necessary to elucidate the full extent of the use of OCT in case of hypomineralisation.